Konsep Marketing Mix Dalam Perspektif Islam - Nasuka, Moh (Bisei : Jurnal Bisnis dan Ekonomi Islam, 2020)
The tendency of the business community now wants maximum profit by justifying any means without considering transcendental moral values. This kind of competitive ethics will result in unfair, professional and sporty competition, harming customers and the worst impact will be that the company will lose customers. Eronically there has been a paradigm shift that today's society considers business behavior using Islamic ethics will hamper the process of achieving maximum profit as a principle of doing business. This phenomenon has invited serious attention for academics and marketing practitioners. This study aims to analyze the concept of marketing mix in an Islamic perspective including products, prices, promotions, distribution, and people, as an alternative concept of strategy in maintaining competition. This type of study is library research. Data collection was carried out using literature related to the research topic. The results of this study conclude that a sharia marketer in serving customers bases the principles of marketing mix in an Islamic perspective sourced from the Koran and as-Sunnah, will be able to provide maá¹£laá¸¥ah (welfare) to customers, so as to create a good relationship between customers and workers sales and with the company in the long run, can ultimately deliver the company more established and sustainable